1975
DOI: 10.1007/bf00273352
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variability of the human chromosomes in two Indian populations ? Rajputs and Punjabis

Abstract: Karotypic evaluation of 100 Rajputs and 100 Punjabis revealed different frequencies of Y chromosome polymorphism and minor chromosome variants. Long Y chromosome were observed 5% of the Rajputs and 3% of the Punjabis. The Y indices of Rajputs were consistently higher than those of Punjabis. Significant differences were noted between Rajputs and Punjabis with respect to the 5 Y indices. Significant differences were also found when those 2 populations were compared with different populations of the world. Minor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Bishop et al inferred that increased length of the Y chromosome might be due to a difference in the degree of contraction of chromosomes during cell division [31]. Gripenberg explained Yqh+ as the result of an addition of chromosomal substance because it bears two secondary constrictions [32], while Ghosh et al concluded that the difference in the size of the Y chromosome is a morphological feature without any functional significance [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bishop et al inferred that increased length of the Y chromosome might be due to a difference in the degree of contraction of chromosomes during cell division [31]. Gripenberg explained Yqh+ as the result of an addition of chromosomal substance because it bears two secondary constrictions [32], while Ghosh et al concluded that the difference in the size of the Y chromosome is a morphological feature without any functional significance [7].…”
Section: Discussionmentioning
confidence: 99%
“…Mattei et al concluded that frequently occurring polymorphisms including Yqh+ do not appear to have any functional or phenotypic effect [6], while Ghosh et al found Yqh+ was highly prevalent in two Indian populations (18% in Rajputs, 19% in Punjabis), and without deleterious effect on the phenotype [7]. Similarly, Rodriguez et al suggested that Y chromosome length variability is polymorphism in human males, unassociated with reproductive problems [8], and Verma et al observed that Yqh+ in fathers may be unrelated to fetal loss [9].…”
Section: Introductionmentioning
confidence: 99%
“…They are located at the centromeres of all chromosomes, most notably at the secondary constrictions of numbers 1, 9 and 16 and at the end of the long arm of the Y chromosome, the region which also stains brightly by &-banding (Paris Conference, 1971). These heterochromatic regions are variable in size without having any overt phenotypic effect and individual differences are heritable (UnnBrus, Fellman & de la Chapelle, 1967;Craig-Holmes, Moore & Shaw, 1973Ghosh & Singh, 1975Miiller, Klinger & Glasser, 1975). The C-bands are stable and found to be unchanged between different tissues (Hoehn et al 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Racial variation in the length of the human Y chromosome was demonstrated by Cohen et al (1966) in a study of Japanese, Asiatic Indians, American Negroes, Jews of Eastern European extraction, and non-Jews of Anglo-Saxon origin. For a good recent review and a comparison of two endogamous Indian groups (Rajputs and Punjabis), see Ghosh and Singh (1975). Cohen et al (1966) also studied the location of the Y chromosome in circular metaphase spreads and found the Y to be peripherally located in 241 of 736 cells (32.7%).…”
Section: Introductionmentioning
confidence: 99%